Pemanfaatan Google Form untuk Mengevaluasi Hasil Belajar Siswa Melalui Pelatihan Guru Smp di SMPT H. Abdul Malik - Sulistyohati, Aprilia; Wiguna, Didik (COVIT (Community Service of Tambusai), 2021)
The digital and technological era has brought a huge shift in conducting tests and evaluations. Tests and evaluations can be carried out using technology to measure abilities in a more efficient and sophisticated way. Currently, several learning activities at SMPT H. Abdul Malik still use conventional methods. Teachers have not been able to make maximum use of technology for carrying out tests; most teachers still use a paper-based system. From the problems above, teacher training is held on utilizing Google forms in learning activities, especially test and evaluation activities. This community service aims to increase the knowledge of SMPT H. Abdul Malik teachers about applying the Google form to measure student learning outcomes. The method used in the implementation of community service uses online drill and practice, where participants listen to the directions and presentations of sources via videos sent by the community service lecturers team, giving examples. Question and answer sessions and discussions are carried out online through the WA group. The stages of implementing community service are the pretest, presentation of material, posttest, and evaluation of activities. Based on the results of the pretest and posttest, it showed that there was an increase in the knowledge of the teachers before and after the Google form training was carried out. Teachers are very interested in applying this knowledge to learning with students. By using Google forms, learning will be more interactive, and teachers feel that this training is very useful for streamlining teacher tasks. This Google form training can be used as a tool for collecting, analyzing, and communicating effectively with students and parents to develop quality education. Keywords: google form, student evaluation, test